Automated Writing Evaluation Tools in the Improvement of the Writing Skill - Parra G., Lorena; Calero S., Ximena (International Journal of Instruction, 2019)
The improvement of the writing skill with the help of modern computer programmes has gained considerable attention in the English as a Foreign Language writing learning process and the better understanding about the contributions of these technological programmes are needed in the field of education. This paper sought to shed light on the effects of implementing free Automated Writing Evaluation tools on the writing performance of the students of an English Teacher Training Programme. Ecuadorian undergraduate learners were encouraged to use Grammark and Grammarly as free Automated Writing Evaluation tools in the improvement of the writing skill as part of the experimentation of this study. These AWE tools were used as complement of teacher´s feedback given to 28 learners on their writing performance during a semester of studies. Quantitative method was used to conduct this practical research by applying a t-test technique and a survey. A pre-test/post-test experimental research design was applied to examine students' improvement on the writing skill. The results revealed positive effects on the improvement of the students writing. This study confirms the benefits of free Automated Writing Evaluation tools in the improvement of the writing skill as it is discussed in the conclusion of this paper followed by some recommendations.